If A+B+C=0 then prove that sin 2A + sin 2B + sin 2C = -4 sinA sinB sinC.
sin 2A + sin 2B + sin 2C = 2 sin ( 2A + 2B )/2 cos ( 2A-2B)/2 + 2 sin C cos C
= 2 sin ( A + B ) cos ( A - B ) + 2 sin C cos C
= 2 sin ( - C ) cos ( A - B ) + 2 sin C cos C [ A+B+C= 0 ]
= - 2 sin C cos ( A - B ) + 2 sin C cos C
= - 2 sin C [ cos ( A - B ) - Cos C ]
= - 2 sin C [ - 2 sin ( A - B +C )/2 sin ( A - B - C )/2]
= - 4 sin C [ - sin ( - 2B )/2 sin ( 2 A ) / 2 ]
= - 4 sin C [ sin B sin A ]
= - 4 sin A sin B sin C = RHS